Insights into the demographic history of african pygmies from complete mitochondrial genomes - Batini, Chiara (2018)
Pygmy populations are among the few hunter-gatherers currently living in sub-Saharan Africa and are mainly represented by two groups, Eastern and Western, according to their current geographical distribution. They are scattered across the Central African belt and surrounded by Bantu-speaking farmers, with whom they have complex social and economic interactions. To investigate the demographic history of Pygmy groups, a population approach was applied to the analysis of 205 complete mitochondrial DNA (mtDNA) sequences from ten central African populations. No sharing of maternal lineages was observed between the two Pygmy groups, with haplogroup L1c being characteristic of the Western group but most of Eastern Pygmy lineages falling into subclades of L0a, L2a, and L5. Demographic inferences based on Bayesian coalescent simulations point to an early split among the maternal ancestors of Pygmies and those of Bantu-speaking farmers (similar to 70,000 years ago [ya]). Evidence for population growth in the ancestors of Bantu-speaking farmers has been observed, starting similar to 65,000 ya, well before the diffusion of Bantu languages. Subsequently, the effective population size of the ancestors of Pygmies remained constant over time and similar to 27,000 ya, coincident with the Last Glacial Maximum, Eastern and Western Pygmies diverged, with evidence of subsequent migration only among the Western group and the Bantu-speaking farmers. Western Pygmies show signs of a recent bottleneck 4,000-650 ya, coincident with the diffusion of Bantu Languages, whereas Eastern Pygmies seem to have experienced a more ancient decrease in population size (20,000-4,000 ya). In conclusion, the results of this first attempt at analyzing complete mtDNA sequences at the population level in sub-Saharan Africa not only support previous findings but also offer new insights into the demographic history of Pygmy populations, shedding new light on the ancient peopling of the African continent.